Effect of carnitine on patients with heart failure: an evidence-based case report - Yosua Yan Kristian; Wiji Lestari (World Nutrition Journal, 2020)
Background: Heart disease is one of the leading causes of death in Indonesia. Nutritional management plays an important role in overcoming heart disease, both as prevention and treatment. Carnitine plays a role in fat metabolism and can reduce the formation of thrombosis, resulting in improved heart function and quality of life of patients.Objectives: This study is aimed to identify the effect of carnitine in patients with heart failure.Methods: Existing research findings and articles are selected based on inclusion and exclusion criteria in three databases, namely PubMed, Cochrane and Wiley. The outcome were functional capacity and heart function.Results: One meta-analysis that address with the clinical questions was obtained, and based on that article, giving carnitine to patients with heart failure has effects on increasing functional capacity, heart function, BNP serum and NT-proBNP levels. However, no effects found on mortality. Furthermore, no significant side effects on carnitine was found.Conclusions: Carnitine supplementation at a dose of 1 up to 6 g/day has a positive impact on functional capacity, heart function, BNP serum and NT-proBNP levels in patients with heart failure, alongside with minimal side effects.